The Causes of Climate Change in Iraq and Steps for Practical Solutions - Potrous, Saad M. (Research Advances in Environment, Geography and Earth Science Vol. 8, 2024)
Iraq was very different two decades ago. Dust fills the air and is stirred up by hot winds. There are vast areas of barren land dotted with stubborn palm trees that struggle patiently to withstand the elements. Climate change in Iraq is having impacts that make Iraq's environment, security, politics, and economic challenges worse, high temperatures, severe drought, declining rainfall, desertification, salinization, and the increased prevalence of dust storms have undermined the agricultural sector in Iraq. In addition, Iraq's water security depends on the deteriorating Tigris and Euphrates river systems. National and regional political uncertainty will make mitigating climate change and addressing transnational water governance very difficult for the state of Iraq for years to come. Greenhouse gas emissions per capita are higher than the global average. Human emissions of greenhouse gases are the primary driver of climate change today. CO2 and other greenhouse gases like methane and nitrous oxide are emitted by burning fossil fuels in Iraq, Annual emissions figures for Iraq; CO2 country profile are often used for contribution to climate change. Climate changes in Iraq due to greenhouse gas emissions lead to a decline in the Ozone layer, and thus the Ultraviolet radiation index that reaches northern, central and southern Iraq is very high. Three steps of solutions are illustrated in this work to address climate change in Iraq for treatment of the burning of associated gas due to oil operations, which contributes effectively and extensively to pollutant gases to the atmosphere, which contribute to the phenomenon of global warming of the atmosphere, as it affects climate change in Iraq and the world. The solutions that are reviewed can be implemented for the purpose of benefiting from the production of liquefied gas for export to support the national economy of Iraq or establishing gas-powered electric generating stations, in addition to developing plans to eliminate gas burning as a measure for environmental safety and preserving the health of humans and other organisms.